Comparison of the Cumulative Live Birth Rates of Progestin-Primed Ovarian Stimulation and Flexible GnRH Antagonist Protocols in Patients With Low Prognosis - Du, Mingze; Zhang, Junwei; Li, Zhen; Liu, Xinmi; Li, Jing; Liu, Wenxia; Guan, Yichun (Frontiers in Endocrinology, 2021)
Objective: To compare the cumulative live birth rate (CLBR) of the progestin-primed ovarian stimulation (PPOS) protocol with that of the flexible GnRH antagonist protocol in patients with poor prognosis diagnosed per the POSEIDON criteria. Methods: This was a retrospective cohort study. Low-prognosis women who underwent IVF/ICSI at the Reproductive Center of Third Affiliated Hospital of Zhengzhou University between January 2016 and January 2019 were included according to the POSEIDON criteria. The CLBR was the primary outcome of interest. The secondary outcome measures were the numbers of oocytes retrieved, 2PN embryos, available embryos and time to live birth. Results: A total of 1329 women met the POSEIDON criteria for analysis. For POSEIDON group 1, the dosage of gonadotropin (Gn) was higher in the PPOS group than in the GnRH antagonist group (2757.3±863.1 vs 2419.2±853.1, P=0.01). The CLBR of the PPOS protocols was 54.4%, which was similar to the rate of 53.8% in the GnRH antagonist group. For POSEIDON group 2, the number of available embryos was higher in the PPOS group (2.0±1.7 vs 1.6±1.4, P=0.02) than in the GnRH antagonist group. However, the CLBRs of the two groups were similar (18.1% vs 24.3%, P=0.09). For POSEIDON groups 3 and 4, there were no statistically significant differences in the number of oocytes retrieved, 2PN, available embryos or CLBR between the two protocols. After adjustments for confounding factors, the CLBR remained consistent with the unadjusted rates. In the POSEIDON group 1 population, the GnRH antagonist protocols had a shorter time to live birth (P=0.04). Conclusion: For low-prognosis patients diagnosed per the POSEIDON criteria, the CLBR of PPOS protocols is comparable to that of GnRH antagonist protocols. In the POSEIDON group 1 population, the GnRH antagonist protocols resulted in a shorter time to live birth.